Redução catalítica seletiva de óxidos de nitrogênio sobre hematita contendo cobre - Ferreira, Hadma Sousa (2007)
The activity of copper-doped hematite in the SCR with propane, in the presence of oxygen, was evaluated in this work. It was found that copper sulfate led to the production of solids with different specific surface areas depending on the amount of copper. The sulfur and copper species were mainly located on the surface. The copper-containing catalysts were more active in the reduction of nitrogen oxides and less active in the propane oxidation as compared to pure hematite. This behavior was assigned to an association of both sulfur and copper species to produce new sites active for NO reduction.